Retrospective chart review demonstrating effectiveness of bimodal neuromodulation for tinnitus treatment in a clinical setting - Emily E. McMahan; Hubert H. Lim (Communications Medicine)
Abstract Background Bimodal neuromodulation combining sound therapy with electrical tongue stimulation using the Lenire® device is emerging as an effective treatment for tinnitus. Methods A single-arm retrospective chart review of 220 patients with tinnitus from the Alaska Hearing & Tinnitus Center examines the real-world outcomes of the recently FDA-approved Lenire treatment. To the best of our knowledge, this is the first assessment of Lenire from a real-world clinic in the United States. The primary endpoint examines the responder rate and mean change in Tinnitus Handicap Inventory (THI) after ~12 weeks of treatment in eligible patients with moderate or worse tinnitus. A responder represents a THI improvement of greater than seven points (i.e., minimal clinically important difference, MCID). Results Here we show that, out of 212 patients with available data, there was a high responder rate of 91.5% (95% CI: 86.9%, 94.5%) with a mean improvement of 27.8 ± 1.3 (SEM) points, and no device-related serious adverse events. Furthermore, a THI MCID of seven points represents a consistent criterion for clinical benefit based on evidence from clinical practice settings. Conclusions These findings show that the Lenire device can be used to safely and effectively reduce tinnitus in a real-world clinical setting.